COVID‐19 and sarcopenia-related traits: a bidirectional Mendelian randomization study - Liu, Chao; Liu, Ningyuan; Zeng, Yi; Xiao, Bo; Wang, Pingxiao; Zhou, Chuqiao; Xia, Yu; Zhao, Ziyue; Xiao, Tao; Li, Hui (Frontiers in Endocrinology, 2023)
Background: Emerging evidence suggested that coronavirus disease 2019 (COVID-19) patients were more prone to acute skeletal muscle loss and suffer sequelae, including weakness, arthromyalgia, depression and anxiety. Meanwhile, it was observed that sarcopenia (SP) was associated with susceptibility, hospitalization and severity of COVID-19. However, it is not known whether there is causal relationship between COVID‐19 and SP-related traits. Mendelian randomization (MR) was a valid method for inferring causality. Methods: Data was extracted from the COVID‐19 Host Genetic Initiative and the UK Biobank without sample overlapping. The MR analysis was performed with inverse variance weighted, weighted median, MR-Egger, RAPS and CAUSE, MR-APSS. Sensitivity analysis was conducted with MR-Egger intercept test, Cochran’s Q test, MR-PRESSO to eliminate pleiotropy. Results: There was insufficient result in the MR-APSS method to support a direct causal relationship after the Bonferroni correction. Most other MR results were also nominally consistent with the MR-APSS result. Conclusions: Our study first explored the causal relationship between COVID-19 and SP-related traits, but the result indicated that they may indirectly interact with each other. We highlighted that older people had better absorb enough nutrition and strengthen exercise to directly cope with SP during the COVID-19 pandemic. Keywords: COVID‐19, sarcopenia, mendelian randomization, long COVID-19, aging.